Kaum Muda, Pendidikan Agama dan Globalisasi: Pendidikan Agama Islam dan Budi Pekerti yang Inklusif dan Toleran - Pranoto, Stepanus Sigit (Yayasan Sukma, 2018)
Dealing with radical understandings in religion, religious education in schools is an alternative to counteracting it. Lack of true religious knowledge, lack of social awareness and low levels of parental supervision and mentoring are thought to be a factor in increasing radical understanding, especially among young people. Therefore religious education in schools needs to be directed to take part in overcoming it by providing inclusive and tolerant material for students. This research aims to see how the government strives for an inclusive and tolerant model of religious education. By reading and analyzing the material in the book Pendidikan Agama Islam dan Budi Pekerti for elementary and secondary schools, this study shows that the government has attempted to provide inclusive and tolerant religious education.